Novel Micro-nano Investigative Approach for Analyzing Critical Properties of Lithium Slag Geopolymer Composites - Javed, Usman (Curtin University, 2024)
This doctoral thesis explores micro-nanoscale optimization of eco-friendly lithium slag geopolymer (LSG) composites, aiming for safe disposal of lithium slag through geopolymer synthesis. Thermo-mechanical optimisation of lithium slag produced binary LSG composites with C-(N)-A-S-H gel and hydroxy-sodalite crystals attributing strength development. The induced reactivity of lithium slag, along with chemical modifiers, improved the compressive strength of LSG composites. Binary blends of LSG composites have compressive strength over 40MPa, improved corrosion resistance against strong acids, and thermal stability at elevated temperatures; therefore, LSG composites may have applications in various structural configurations.